2019
DOI: 10.3390/nu11010110
|View full text |Cite
|
Sign up to set email alerts
|

Tributyrin in Inflammation: Does White Adipose Tissue Affect Colorectal Cancer?

Abstract: Colorectal cancer affects the large intestine, leading to loss of white adipose tissue (WAT) and alterations in adipokine secretion. Lower incidence of colorectal cancer is associated with increased fibre intake. Fructooligosaccharides (FOS) are fibres that increase production of butyrate by the intestinal microbiota. Tributyrin, a prodrug of butyric acid, exerts beneficial anti-inflammatory effects on colorectal cancer. Our aim was to characterise the effects of diets rich in FOS and tributyrin within the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…TB supplementation significantly decreases the levels of TNF-a in the plasma of rats after LPS administration (47). Studies have reported that TB supplementation can increase the levels of IL-10 in retroperitoneal adipose tissue (46) and colitis+TBT mice (16), and the content of TGF-b is also increased by TB supplementation in experimental colitis (16). These results are consistent with our results and indicate that TB supplementation can improve immunocompetence by regulating the production of inflammatory cytokines.…”
Section: Effect Of Tb Supplementation On Immunocompetencesupporting
confidence: 91%
See 2 more Smart Citations
“…TB supplementation significantly decreases the levels of TNF-a in the plasma of rats after LPS administration (47). Studies have reported that TB supplementation can increase the levels of IL-10 in retroperitoneal adipose tissue (46) and colitis+TBT mice (16), and the content of TGF-b is also increased by TB supplementation in experimental colitis (16). These results are consistent with our results and indicate that TB supplementation can improve immunocompetence by regulating the production of inflammatory cytokines.…”
Section: Effect Of Tb Supplementation On Immunocompetencesupporting
confidence: 91%
“…Similarly, various previous studies have reported that TB or butyric acid supplementation in feed can also increase the production of immunoglobulins ( 13) and IFN-g (44). Furthermore, IL-10 and TGF-b are two important antiinflammatory cytokines (16,46), and TNF-a and IL-8 are two important pro-inflammatory cytokines (46). In the present study, 0.06% and 0.09% TB supplementation in feed significantly increased the levels of IL-10 and TGF-b and s i g n i fi c a n t l y d e c r e a s e d t h e l e v e l s o f T N F -a .…”
Section: Effect Of Tb Supplementation On Immunocompetencementioning
confidence: 84%
See 1 more Smart Citation
“…84 Biondo et al observed that a tributyrinsupplemented diet led to increased VEGF levels in white adipose tissue (WAT) in mice, with a diminished concentration of serum leptin caused by colon carcinogenesis. 85 In leptin-deficient ob/ob mice, lactoferrin administration led to upregulation of the expression of HIF-1A and VEGF genes. 86 In genetically obese leptin receptor-deficient diabetic mice, human amniotic membrane upregulated VEGF and promoted the healing of complex chronic wounds.…”
Section: Animal Studiesmentioning
confidence: 99%
“…At the point where diet-derived signals intersect, white adipose tissue (AT) is now regarded as the major endocrine organ in the body and performs an integral function in maintaining metabolic and immunological homeostasis. 22 Up to date, various research reports have investigated the effect of diet/nutrition in CRC, with findings showing that it may perform both a causative and a preventive role in tumor growth. Apart from being a known risk factor for CRC, increased adiposity is also associated with poorer outcomes.…”
Section: Rectummentioning
confidence: 99%